Measurement of C-2 radical density in microwave methane/hydrogen plasma used for nanocrystalline diamond film formation - Hiramatsu, M; Kato, K; Lau, C; Foord, J; Hori, M (2003)
C2 radical density in a conventional microwave plasma-enhanced chemical vapor deposition (MWPCVD) with CH4/H2 mixture was measured using absorption spectroscopy. At the typical growth conditions for MWPCVD used for nanocrystalline diamond formation, C2 radical density in the plasma was of the order of 1012 cm-3. Correlation between nanocrystalline diamond growth and C2 radical density was discussed. © 2002 Elsevier Science B.V. All rights reserved.